Model Pengembangan Sistem Informasi Berbasis Technology Acceptance Model Dan Technology Ajax Pada Koperasi Simpan Pinjam - Adiyuda Prayitna; FX. Henry Nugroho (AITI, 2017)
Koperasi Simpan pinjam (KSP) is an micro financial firm, mostly serve for micro business in contry side of indonesia, their consumer is low income people. KSP bring relatively easy financial support with easy requirement for loan and credit interest. Unfortunately this firm not well managed, so business improvement, financial management and bussiness report not in a good perform, this is expressed by accounting and financial report still using conventional model, by a book general ledger and/or by computer software mostly Microsoft Excell. This research focuse to solve accounting report with automatic system, developed by Technology Acceptance Model and AJAX Programming.